2017
DOI: 10.3892/etm.2017.4686
|View full text |Cite
|
Sign up to set email alerts
|

In-hospital and long-term outcomes of congestive heart failure: Predictive value of B-type and amino-terminal pro-B-type natriuretic peptides and their ratio

Abstract: Abstract. Relative changes in B-type natriuretic peptide (BNP) and amino terminal pro-BNP (NT-proBNP) levels may help to assess the risk of congestive heart failure (CHF). However, whether these levels at the time of admission enable the prediction of outcomes with acute exacerbation remains unknown. The current study determined the abilities of BNP, NT-proBNP and their ratio to predict in-hospital and long-term outcomes of patients with CHF. Patients who were admitted to the cardiac care unit of Juntendo Univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…In this study, higher NT-proBNP levels were linearly associated with a beneficial lipoprotein profile, including lower very low-density lipoprotein (VLDL), intermediate-density lipoprotein (IDL), and LDL-particles along with higher large HDL particle measures, lower small dense HDL particle measures and lower TG. Instead, the other study showed a negative correlation between LDLc and NT-proBNP/BNP ratio on 195 in-patients with acute heart failure (Rho = −0.36, p < 0.01) 68 .
Figure 1Flow-chart showing the study selection process.
…”
Section: Resultsmentioning
confidence: 99%
“…In this study, higher NT-proBNP levels were linearly associated with a beneficial lipoprotein profile, including lower very low-density lipoprotein (VLDL), intermediate-density lipoprotein (IDL), and LDL-particles along with higher large HDL particle measures, lower small dense HDL particle measures and lower TG. Instead, the other study showed a negative correlation between LDLc and NT-proBNP/BNP ratio on 195 in-patients with acute heart failure (Rho = −0.36, p < 0.01) 68 .
Figure 1Flow-chart showing the study selection process.
…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, with changes in people's lifestyle and diet structure, the occurrence and development of cardiovascular diseases show an increasing trend, and onset age is also becoming younger ( 10 ). In addition, there are increasing number of inducements of heart failure, so the morbidity of heart failure is getting higher and higher, seriously threatening the life and health of humans ( 11 ). Patients with early heart failure only have complaints such as fatigue, decreased exercise tolerance and increased heart rate, which can easily be ignored ( 12 ), but with the prolonged course of disease and the aggravation of disease, patients may show manifestations including dyspnea on exertion, orthopnea, lung rale and even pink frothy sputum, which can reduce cardiac function and increase difficulties in treatment ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Existing evidence su ggests that ACM may elevate the risk of embolism through various mechanisms such as left atrial systolic dysfunction, endothelial damage, and hypercoagulability 3) . While previous large-scale studies have indicated the significance of ACM markers in gauging the risk of adverse cardiac events, such as atrial fibrillation (AF) 22,23) , myocardial infarction (MI) 24,25) , and HF 26) , their role in st roke prognosis remains underexplored. Several small-sample retrospective studies have found that some ACM-related markers are associated with death and disability after IS 11,12) .…”
Section: Survival Analysis Of Acm In Patients With Noncardioembolic S...mentioning
confidence: 99%